Kekuatan Hukum Akta Jual Beli Tanah yang Dibuat PPAT (Studi Kasus Putusan Kasasi MA No. 787 K/Pdt/2013) - Sigit Dwi Santoso (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2018)
Land issues are an issue that always arises and always actual from time to time. One of the land issues is a land dispute case that occurred in Sleman district, which has been examined and issued a decision on appeal with Supreme Court verdict. 787 K/Pdt/2013 on December 17, 2013, of which one of its decisions is